PENGARUH PARIWISATA TERHADAP PERALIHAN FUNGSI TANAH PEKARANGAN DESA (PKD) (STUDI DI DESAPAKRAMAN PADANGTEGAL, UBUD, GIANYAR) - Mendrawan, Gusti Ngurah; Wita, I Nyoman; Ari Atu Dewi, A. A. Istri (Kertha Desa, 2014)
The land is importan for the society, economic value of land is very high at tourismobject area. Customary village of Padang Tegal is famous tourism object with naturalenvironment and its culture. From this background can be formulated the issues asfollows: how is position and function of village land (PKD) at customary village ofPadangtegal? How is effect of tourism toward function change of village land PKD) atcustomary village of Padangtegal. The research method have been applied wasempirical research that are law research which concepted as emperical symptom whichcan be seen in reality life. Analysis was conducted in qualitative and presented analysisdescriptively. Conclusion of this study as follows: position of land at customary villageof Padangtegal practically have very strong position and function of land at customaryvillage of Padangtegal have function of religious. Existence of tourism have effecttoward function change of village land (PKD). From function change have effect topublic economic and social.
Keywords: tourism, village land (PKD)